2022
DOI: 10.1002/jbm.b.35028
|View full text |Cite
|
Sign up to set email alerts
|

Prefabrication technique by preserving a muscular pedicle from masseter muscle as an in vivo bioreactor for reconstruction of mandibular critical‐sized bone defects in canine models

Abstract: In vivo bioreactors serve as regenerative niches that improve vascularization and regeneration of bone grafts. This study has evaluated the masseter muscle as a natural bioreactor for βTCP or PCL/βTCP scaffolds, in terms of bone regeneration. The effect of pedicle preservation, along with sole, or MSC‐ or rhBMP2‐combined application of scaffolds, has also been studied. Twenty‐four mongrel dogs were randomly placed in six groups, including βTCP, βTCP/rhBMP2, βTCP/MSCs, PCL/βTCP, PCL/βTCP/rhBMP2, and PCL/βTCP/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…A similar improvement was obtained by Nokhbatolfoghahaei et al and Park et al, who seeded MSCs and TMSCs on PCL/ β ‐TCP scaffolds, showing quantitatively the improvement in bone regeneration (15.430% ± 0.547% and 5.813% ± 1.345%), compared to scaffolds alone or scaffolds combined only with growth factors. [ 39,40 ] Finally, Temple et al and Roskies et al have proven the efficacy of the seeding of ACSCs aggregates on both PCL (Figure 8C) and PEKK (Figure 8D) scaffolds, showing a higher cell infiltration in the seeded scaffolds after 7 days of in vivo implantation. [ 48,49 ]…”
Section: Cell Therapymentioning
confidence: 98%
See 3 more Smart Citations
“…A similar improvement was obtained by Nokhbatolfoghahaei et al and Park et al, who seeded MSCs and TMSCs on PCL/ β ‐TCP scaffolds, showing quantitatively the improvement in bone regeneration (15.430% ± 0.547% and 5.813% ± 1.345%), compared to scaffolds alone or scaffolds combined only with growth factors. [ 39,40 ] Finally, Temple et al and Roskies et al have proven the efficacy of the seeding of ACSCs aggregates on both PCL (Figure 8C) and PEKK (Figure 8D) scaffolds, showing a higher cell infiltration in the seeded scaffolds after 7 days of in vivo implantation. [ 48,49 ]…”
Section: Cell Therapymentioning
confidence: 98%
“…[ 42 ] Nokhbatolfoghahaei et al have also tested β ‐TCP scaffolds in several conditions in a canine animal model, and always reported higher histomorphometry values of NB in the presence of rh‐BMP‐2 (NB = 48.443 ± 0.250%). [ 39 ] On the other hand, despite reporting a modest trend of bone formation for PCL/ β ‐TCP scaffolds soaked into a BMP‐2/collagen solution (BV/TV ≈ 13%), results of Lee et al lacked statistical significance when compared to the control group (PCL/ β ‐TCP alone). [ 36 ] Similar outcomes were reported in another PCL/ β ‐TCP scaffold study, where intra‐scaffold injections of a rhBMP‐2 and bdECM bioink improved bone‐to‐implant contact ratio (BIC) (BIC = 51.29 ± 14.64%), but NB was again not significantly ameliorated.…”
Section: Bioactive Molecules For Mandibular Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…To address these obstacles, a novel approach involves the in vivo implantation of a scaffold into an ectopic site such as skin or muscle, termed an in vivo bioreactor (IVB), with subsequent transfer of the newly vascularized scaffold into the bony site of interest [ 58 , 59 , 60 , 61 , 62 ]. To date, many preclinical studies have demonstrated robust bone healing responses using the IVB method [ 63 , 64 , 65 , 66 ]. The majority of IVB use in humans involves grafting periosteum along with its vascular supply to the site of interest [ 67 , 68 , 69 , 70 ], but actual prefabrication techniques involving ectopic maturation of a scaffold with subsequent transfer to the site of interest are rare in clinical studies.…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%